Institutional influences in the Maghreb region for Czech aircraft exports - Nikiforova, Vitaliia (2025)
This diploma thesis explores the role of institutional factors in shaping the competitiveness of Czech aircraft exports in the Maghreb region. By combining theoretical insights from institutional economics and international trade with practical field-based observations, the study seeks to identify how key institutional dimensions influence export performance in four North African countries: Algeria, Libya, Morocco, and Tunisia. The research is structured into three main chapters. The first chapter provides the theoretical framework and justifies the selection of six core institutional indicators: trade agreements, corruption, foreign direct investment, political stability, economic freedom, and market access. The second chapter applies these dimensions in a comparative analysis of the Maghreb countries, using macroeconomic data and aviation market characteristics to assess each country’s environment for aircraft trade. The third chapter adopts a scenario-based methodology to model plausible export strategies under varying institutional and market conditions. Scenarios are derived from the author’s direct professional experience in aerospace exports and logical extrapolation of regional needs and sectoral trends. The findings show that Czech aircraft exports are competitively positioned in the Maghreb, however, competitiveness is not static. It is highly contingent on institutional compatibility, market readiness, and the exporter’s ability to adapt to local constraints.